Approaches to the chemical synthesis of the chlorosulfolipids - Chung, Won-Jin; Vanderwal, Christopher D (Accounts of chemical research, 2014)
Since the initial discovery of the chlorosulfolipids in 1969, the chemical synthesis community largely ignored these compounds for nearly four decades, perhaps because they contain a high density of chlorine atoms, which suggested that these molecules and any projected synthetic intermediates might be unstable. Beginning in 2008, a sudden flurry of synthesis activity by several research groups, including our own, appeared in the literature. In this Account, we highlight our work from the last several years on the chemical synthesis of the chlorosulfolipids. Our work in this area began with attempts to stereoselectively generate the abundant dichloroalcohol functional group arrangements in these natural targets. In these early studies, we learned that many polychlorinated intermediates were far more stable than anticipated. We also developed a method for the diastereoselective dichlorination of allylic alcohol derivatives that permitted access to the syn,syn-dichloroalcohol stereotriad found in several chlorosulfolipids. Concurrently, we investigated an approach to mytilipin A that included multiple intermediates bearing aldehydes with β-leaving groups, but this route proved intractable. However, we leveraged what we had learned from this approach into our first success in this area: we synthesized danicalipin A via a route that introduced all of the polar functional groups using alkene oxidation reactions. By adapting this relatively general strategy, we completed an enantioselective synthesis of malhamensilipin A. This body of work also resulted in the full stereochemical elucidation of danicalipin A and the structural revision of malhamensilipin A. Finally, with the advent of Z-selective alkene cross metathesis, we developed a second-generation synthesis that featured this strategy in place of a poorly performing Wittig olefination that plagued our first approach. In addition to this new convergent step, we developed a reliable protocol for diastereoselective addition to highly sensitive α,β-dichloroaldehydes and a method for kinetic resolution of complex vinyl epoxides. Altogether, these advances led to a synthesis of enantioenriched mytilipin A in only eight steps. In the context of this work, we discovered a number of highly stereoselective reactions that might offer new, broadly applicable lessons in acyclic stereocontrol. Moreover, this research testifies to the stability of polychlorinated molecules and should inspire confidence in the use of aliphatic chlorides in other applications, including in discovery chemistry.